Interleukin‐7 receptor α‐chain haplotypes differentially affect soluble IL‐7 receptor and IL‐7 serum concentrations in children with type 1 diabetes. Issue 5 (13th March 2018) - Seyfarth, Julia; Lundtoft, Christian; Förtsch, Katharina; Ahlert, Heinz; Rosenbauer, Joachim; Baechle, Christina; Roden, Michael; Holl, Reinhard W; Mayatepek, Ertan; Kummer, Sebastian; Meissner, Thomas; Jacobsen, Marc
Abstract : Background: Interleukin‐7 receptor α‐chain ( IL7RA ) haplotypes are associated with susceptibility for development of autoimmune diseases, including type 1 diabetes (T1D). A protective IL7RA haplotype which causes lower soluble IL‐7R (sIL‐7R) serum levels is hypothesized to restrict IL‐7‐availability for self‐reactive T cells. Functional mechanisms affected by a risk‐associated IL7RA haplotype are unknown. Methods: We investigated the influence of IL7RA haplotypes (tagged by rs6897932T for the protective or by rs1494555G for the risk haplotype) on sIL‐7R and IL‐7 serum concentrations as well as disease manifestation of children with T1D ( n = 259). Possible effects of differential IL‐7 serum concentrations on IL‐7‐mediated in vitro T cell functions (i.e. IL‐7R regulation and cytokine expression) were measured in a second study group of children with T1D ( n = 42). Results: We detected lower sIL‐7R serum concentrations in children with T1D carrying protective or risk haplotypes as compared to reference haplotypes. sIL‐7R levels were lowest in T1D children with the protective haplotype and lower IL‐7 serum levels were exclusively detected in this study group. We found no evidence for dependency between IL‐7 and sIL‐7R serum concentrations and no association with T1D manifestation. Neither IL‐7 nor sIL‐7R serum levels were associated with mIL‐7R regulation or IL‐7‐promoted T cell cytokine expression. Conclusions: Children with T1D carrying autoimmunity risk‐ or protection‐associated IL7RA haplotypes had both lower sIL‐7R serum concentrations as compared to the reference haplotype, but only T1D children with the protective haplotype had lower IL‐7 serum levels. Our results suggest additional functional mechanisms of autoimmunity‐associated IL7RA variants independent from sIL‐7R mediated regulation of IL‐7 availability for T cells.